Demencia debido a la enfermedad de Huntington en el adultez. - Bohórquez Vera, Laura Victoria (My University, 2019)
dementia caused by Huntington's disease is a problem that is present in some countries of the world, unlike other medical diseases caused by dementia, this disease has no prevalence worldwide, the pathological indicators that direct to diagnose this type of disorder in patients, they are mentioned with the presence of significant short and long-term memory impairment, difficulty in language comprehension, moderate psychomotor retardation and involuntary psychomotor movements such as dancing in the trunk and upper limbs, choreiform movements movements repetitive involuntary and bradykinesia slow movements. Korea is an involuntary movement disorder, hyperkinetic type, characterized by spontaneous movements, without purpose, excessive, abrupt, arrhythmic, unsupported, irregular in time, distributed randomly, with changes in speed and direction, which migrate from one part from body to body, giving the appearance of dance. The present trial aims to identify the pathological indicators of dementia due to Huntington's disease through the exposure of a clinical case, through the literature review, to optimize knowledge in caregivers and affected people in order to improve their care accordinglyThe specific objectives are related to the description of the theoretical aspects of dementia due to Huntington's disease and to identify the pathological indicators of dementia due to Huntington's disease through case exposure
La demencia ocasionada por la enfermedad de Huntington es una problemática que se encuentra presente en algunos países del mundo, a diferencia de otras enfermedades médicas originadas por demencia, esta enfermedad no tiene prevalencia a nivel mundial, los indicadores patológicos que direccionan a diagnosticar este tipo de trastorno en los pacientes, se mencionan con presencia de un deterioro significativo de la memoria a corto y largo plazo, dificultad en la comprensión del lenguaje, retardo psicomotor moderado y movimientos involuntarios psicomotor como baile en el tronco y los miembros superiores, movimientos coreiforme movimientos involuntarios repetitivos y bradiscinesia lentitud de los movimientos. La corea es un trastorno involuntario del movimiento, tipo hipercinético, caracterizado por movimientos espontáneos, sin propósito, excesivos, abruptos, arrítmicos, no sostenidos, irregulares en tiempo, distribuidos en forma aleatoria, con cambios en velocidad y dirección, que migran de una parte del cuerpo a otra, dando la apariencia de danza. El presente ensayo pretende identificar por medio de la exposición de un caso clínico los indicadores patológicos de la demencia debido a la enfermedad de Huntington, a través de la revisión bibliográfica, para optimizar conocimientos en cuidadores y personas afectadas con el propósito de mejorar su atención los objetivos específicos están relacionados con la descripción de los aspectos teóricos sobre la demencia debido a la enfermedad de Huntington e identificar por medio de la exposición de un caso los indicadores patológicos de la demencia debido a la enfermedad de Huntington
Keywords: DEMENCIA; ENFERMEDAD; HUNTINGTON; ADULTEZ